A gentleman ought to know - Ashford, Jane (Ashford, Jane. Duke's estates, 2023)
Back home in Leicestershire after her first London season, Charlotte Deeping, needing something to keep her occupied, digs into the mystery surrounding the arrival of the Marquess of Glendarvon, which rouses an old vendetta--and a love to last a lifetime.